From the countryside to the world: in search of a continental internationalism for the MST – An interview with Gilmar Mauro - Rubbo, Deni (Pontifícia Universidade Católica de São Paulo, 2012)
In this interview, conducted at the Florestan Fernandes National School (ENFF) in Guararema,São Paulo in November 2011, Gilmar Mauro, national leader of the MST, discusses a topic thatcontinues to be theoretically and politically challenging: internationalism, with a special focuson Latin America. He talks about how that process and principle have been a constant concernin the historical trajectory of the MST, whether it be in training courses, relations with otherpopular rural organizations, in the camps and settlements, or in the creation of innumerablesolidarity brigades.